2020
DOI: 10.1101/2020.06.04.134692
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct genetic pathways define pre-leukemic and compensatory clonal hematopoiesis in Shwachman-Diamond syndrome

Abstract: Shwachman-Diamond syndrome (SDS) is an inherited bone marrow failure syndrome with predisposition to developing leukemia. We found that multiple independent somatic hematopoietic clones arise early in life, most commonly harboring heterozygous mutations in EIF6 or TP53. EIF6 mutations cause functional compensation for the germline deficiency by alleviating the SDS ribosome joining defect, improving translation, and reducing p53 activation.TP53 mutations decrease checkpoint activation without affecting ribosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 55 publications
(52 reference statements)
0
16
0
Order By: Relevance
“…A recent study from the North American Shwachman-Diamond Syndrome Registry identified highly recurrent somatic EIF6 mutations in bone marrow samples from SDS patients but not from patients with other IBMFSs or predisposition syndromes (DC, GATA2 deficiency syndrome, or germline SAMD9/SAMD9L mutations) or sporadic AML. 72 In functional analyses, these EIF6 mutations were shown to disrupt EIF6:60S binding interaction or destabilize EIF6 protein, resulting in improved 80S maturation and global protein synthesis and a reduction in aberrant p53 activation. Overall, somatic clones were infrequent in the first several years of life but approached ubiquity in the second decade and beyond, and most commonly involved 1 of only 4 genes (EIF6, TP53, PRPF8, and CSNK1A1).…”
Section: Sdsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from the North American Shwachman-Diamond Syndrome Registry identified highly recurrent somatic EIF6 mutations in bone marrow samples from SDS patients but not from patients with other IBMFSs or predisposition syndromes (DC, GATA2 deficiency syndrome, or germline SAMD9/SAMD9L mutations) or sporadic AML. 72 In functional analyses, these EIF6 mutations were shown to disrupt EIF6:60S binding interaction or destabilize EIF6 protein, resulting in improved 80S maturation and global protein synthesis and a reduction in aberrant p53 activation. Overall, somatic clones were infrequent in the first several years of life but approached ubiquity in the second decade and beyond, and most commonly involved 1 of only 4 genes (EIF6, TP53, PRPF8, and CSNK1A1).…”
Section: Sdsmentioning
confidence: 99%
“…Instead, progression of TP53-mutated clones was mediated by the development of biallelic alterations in the TP53 locus, by deletion, copy neutral loss of heterozygosity, or second point mutation. 72 In functional experiments, TP53 inactivation was shown to enhance the competitive fitness of SBDS-deficient cells by inactivating senescence pathways without correcting the underlying SDS ribosome and translational defects. Consistent with these human genetic observations, loss of TP53 in a mouse model of SDS can uncouple the ribosomal stress caused by SBDS deficiency from activation of cellular senescence pathways, resulting in partial rescue of the SDS phenotype.…”
Section: Sdsmentioning
confidence: 99%
“…Although BMF manifests early in live, MDS and leukemia develop as a secondary disease after a latency of years to decades from diagnosis of the underlying condition [ 5 , [11] , [12] , [13] , [14] , [15] , [16] ]. Clonal evolution is usually associated with a number of recurrent somatic mutations, for example RUNX1 in FA, CSF3R and RUNX1 in SCN, TP53 and EIF6 in SDS, GATA1 short and cohesin genes in Down syndrome [ 5 , 7 , 10 , 12 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. Additional mutations can involve typical leukemia drivers including RAS pathway genes, SETBP1 , ASXL1 , EZH2 , and others.…”
Section: Introduction: Germline Predisposition In Myeloid Neoplasmsmentioning
confidence: 99%
“…As SDS patients can develop multiple independent TP53 mutated clones, serial monitoring by bulk sequencing would fail to distinguish clinically significant sub-clonal changes in TP53 allelic status. These findings imply the value of integrating of single-cell DNA sequencing into surveillance strategies in order to identify patients with high-risk clones [ 40 ]. In MM, single-cell transcriptome analysis revealed that extramedullary progression is associated with alterations in the transcriptional programs of plasma cells and the microenvironment affecting proliferation and immune evasion [ 41 ].…”
Section: Applications Of Single-cell Multi-omics In Hematological mentioning
confidence: 99%